Acquired epidermodysplasia verruciformis in the context of HIV infection with successful antiretroviral therapy; Epidermodisplasia verruciforme adquirida en el contexto de una infección por el VIH en tratamiento antiretroviral exitoso - Aragon-Caqueo, D (Ediciones Doyma, S.L., 2026)
[No abstract available]